Growth performance, carcass characteristics, meat and egg quality, and intestinal microbiota in Beijing-you chicken on diets with inclusion of fresh chicory forage. Issue 1 (2nd January 2019) - Zheng, Mingli; Mao, Peichun; Tian, Xiaoxia; Meng, Lin
Abstract: The aim of this study was to evaluate the effects of fresh chicory forage in chicken diets on growth performance, carcass characteristics, meat and egg quality, as well as intestinal microbiota. A total of 600 healthy 16 weeks female Beijing-you chickens were randomly assigned to four dietary treatments containing 0%, 5%, 8% and 10% chicory forage with six replicate pens and 25 chickens in each replicate. Chickens were raised in a free-range system for 13 weeks after seven days of adaptation. High-throughput sequencing was used to characterise the microbiota in three different intestinal sections (duodenum, ileum and caecum). The results showed that dietary supplementation of chicory forage increased ( p < .05) egg weight, yolk colour, total amino acids and delicious amino acids in muscles, and decreased ( p < .05) abdominal fat yield compared to the control. However, increased ( p < .05) average daily feed intake, increased ( p < .05) feed conversion ratio, increased ( p < .05) mortality and decreased ( p < .05) eggshell strength were observed in chickens fed chicory forage than in those fed a basal diet. Dietary supplementation of chicory forage stimulated the proliferation of the Lactobacillus in ileum and the Bacteroides in caecum, and depressed pathogenic microbes including the Rikenella, thereby further improved intestinal health and nutrient utilisation. It was concluded that 8% chicory forage could be considered as a beneficial feed additive in Beijing-you chicken diets. In addition to the good nutritional profile, medicinal properties were associated with the beneficial effects of chicory forage on chickens. Highlights: Dietary supplementation of chicory forage improved muscle nutritional value and flavour. Dietary supplementation of chicory forage affected egg quality. Dietary supplementation of chicory forage regulated the intestinal microbiota.